Zoom-a program usage guide based on active learning strategies - Baharom, Mohd. Munir (2015)
The usage of Zoom-A web-based teaching materials program has been widely utilized by primary schools throughout Malaysia. The internet-based interactive learning program was launched in 2004 by the Deputy Minister of Education. The program draws positive response from educators as it provides various facilities that are capable of improving student achievement. Through this study, a Zoom-A Program usage guide with active learning strategies has been developed. Three active learning strategies by Simmons & DiStasi are modified and utilized in this study according to student levels and situations i.e. Number Head Together, question and answer together; and the ten two strategy. The number of respondents involves a total of 35 primary school students of Sekolah Kebangsaan Kempas, Johor Bahru. A questionnaire is used as an instrument of research. The reliability value of the instrument is a=0.908, demonstrating high reliability of the questions. The data is analyzed with Statistical Package for Social Sciences (SPSS) 18.0 to gauge frequency, percentage and mean. Through content-based and Zoom-A performance tests, the results elucidate high level of understanding and the advantages of Zoom-A utilization. The t-test also shows different students’ perceptions towards all three activities conducted; while activities done with ten two strategy demonstrate the highest mean by comparison. Some recommendations are presented to improve the effectiveness in learning science so that the students involved will demonstrate academic progress and improvement through the usage of Zoom-A Program with active learning activities combined.